Characteristics and lipid lowering treatment patterns in patients tested for lipoprotein(a): A real-world US study - Xingdi Hu; Joaquim Cristino; Raju Gautam; Rina Mehta; Diana Amari; Ji Haeng Heo; Siwei Wang; Nathan D. Wong (Elsevier, 2023)
Objective: Elevated lipoprotein(a) [Lp(a)] is a risk factor for atherosclerotic cardiovascular disease (ASCVD) and has no approved pharmacotherapies. Limited real-world data exists on the proportion of patients with available Lp(a) test results, characteristics of these patients, and their use of lipid lowering therapies (LLTs) for secondary prevention (SP) and primary prevention (PP) of ASCVD. Methods: Patients with measured Lp(a) receiving LLTs for SP or PP of ASCVD were identified in the Optum Clinformatics® Data Mart database. Lp(a) distribution and LLT utilization including persistence and adherence were assessed. Logistic regression was used to assess the association between Lp(a) levels and low-density lipoprotein cholesterol (LDL-C) levels after index LLT, adjusting for baseline characteristics. Results: Overall, 2154 SP and 7179 PP patients met eligibility criteria. Of patients with available laboratory data, only 0.7% (SP) and 0.6% (PP) had Lp(a) test results. In the SP cohort, Lp(a) levels ≥125 nmol/L and ≥175 nmol/L were 26.4% and 17.6%, respectively, and the mean (SD) Lp(a) levels (overall SP cohort 90.4 [97.9] nmol/L) were highest in Black patients (123.4 [117.4]; p<0.001). Statin monotherapy was the most frequently prescribed LLT in SP patients overall (89.4%). Median (interquartile range [IQR]) persistence of LLTs was 227 (91, 649) days and 33.6% achieved ≥80% proportion of days covered (PDC). Patients with Lp(a) ≥175 nmol/L had 2.1 times greater odds of having elevated LDL-C (≥70 mg/dL) post-LLT than those with Lp(a) <175 nmol/L (p = 0.031). Similar findings were observed in the PP population. Conclusions: Lp(a) screening was rare. Elevated Lp(a) was observed in more than one-quarter of patients receiving LLTs, with the highest mean Lp(a) levels observed in Black patients. Low adherence to LLTs was prevalent and at least half of patients failed to achieve their respective LDL-C target thresholds despite treatment. Finally, high Lp(a) levels were associated with worse LDL-C control.